ANALISIS KEBOCORAN RADIATOR DAN CARA MENGATASINYA PADA DUMP TRUCK - -, Wachidin; Budi, Bagus Setia (Jurnal TEDC; Vol 20 No 1 (2026): JURNAL TEDC, 2026)
The rapid development of heavy equipment technology involves complex systems, notably the cooling system, which is crucial for maintaining optimal engine operating temperatures. High thermal energy generated during combustion must be effectively managed to prevent engine failure. The radiator serves as the primary component in this process, yet it frequently experiences performance degradation due to neglected periodic maintenance and aging factors. This study aims to identify the specific causes of radiator damage, particularly leakage phenomena, and to analyze its impact on the engine's optimal operating temperature, which typically ranges from 75°C to 90°C. The research employed technical observation and component analysis of the radiator. The investigation focused on component replacement schedules and the chemical reactions between the coolant and radiator materials that lead to corrosion and material erosion. The findings indicate that radiator leakage is primarily caused by improper maintenance schedules and chemical reactions resulting from the accumulation of compounds within the coolant. Unaddressed damage without routine inspection potentially leads to overheating, which impairs engine performance and results in extensive, irreparable damage. Therefore, disciplined periodic inspections are highly recommended to ensure sustained engine performance stability.